Lenin: NEP, egemonia e transizione - Fresu, Gianni (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2018)
At the beginning of 1921, the Soviet state was in a very unfavorable situation in which the destructions of the First World War were added to those of the civil war, leading to a dramatic economic crisis. At the X Congress of the Russian Communist Party, Lenin explained for the first time the need to give the country a profound change in economic policy. Even for the defeat of the revolution in Western Europe, simultaneously with the turn of the Comintern towards the “United Front” and the direct support for anti-colonial struggles, it became necessary to develop socialism at the national level. The NEP meets the need for an organic alliance between the socialist economy and the peasantry, between industry and the countryside, necessary for the survival of the revolution itself. It should therefore be considered not only as a measure of economic policy, but as a hegemonic choice with a specific political objective: the economic and social alliance between the working class and peasants in the construction of socialism, with the aim of limiting as far as possible , the use of coercive means by Soviet power. Keywords: Lenin; New Economical Politicy; Hegemony; Socialist Transition.